Developing Oral Fluency in English: EFL Teachers’ Understanding, Self-Reported Practices, and Textbook Support - Lina María Robayo Acuña (Profile: Issues in Teachers' Professional Development)
This qualitative study examined the understanding of oral fluency among nine Colombian EFL teachers, their practices for promoting it, and the extent to which their classroom EFL textbooks support the development of oral fluency. Data were gathered through semi-structured interviews and a content analysis of textbooks. The findings evidenced that the teachers define fluency as both parallel to overall English proficiency and as an aspect of speech production narrowly related to the cognitive, utterance, and perception aspects of fluency. Furthermore, teachers reported a wide range of fluency activities proven beneficial by research, although their course textbooks seem not to sufficiently foster oral fluency. These results suggest that teachers’ fluency definitions are not dichotomous, highlighting the need to relate teachers’ cognitions of fluency with theoretical accounts.